ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI JAGUNG DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Dian Komala Sari; Dwi Haryono; Novi Rosanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The purpose of this research are to analyze of household income and the prosperity grade corn farmers in the District of South Lampung regency. This research was done in Muara Putih Village, Merak Batin Village, and Krawang Sari Villag of Natar district, South Lampung regency using stratified random sampling.  There were 51 corn farmers involved in this research. The result research showed that corn farmer household income as much as Rp23.791.838,24/years. The household income derived from farming and non farming of corn (on farm) was Rp20.566.348,04/years, income from nonfarm activites (off farm) was Rp707,647.06/years, and revenues from non-agriculture (nonfarm) was Rp2.517.843,14/years. Based on the BPS criteria, corn farmers household at Natar were categorized as prosperous as many as 70,59 percent and are not prosperous as many as 29,41 percent, while based on the Sajogjo criteria, corn farmers in Natar were categorized as sufficient 60,78 percent, almost poor 15,69 percent, and including decent life 23,53 percent. Keywords: corn farming, household income, poverty, prosperity grade